Persisting inequalities in survival patterns of childhood neuroblastoma in Southern and Eastern Europe and the effect of socio-economic development compared with those of the US. (June 2018) - Panagopoulou, Paraskevi; Georgakis, Marios K.; Baka, Margarita; Moschovi, Maria; Papadakis, Vassilios; Polychronopoulou, Sophia; Kourti, Maria; Hatzipantelis, Emmanuel; Stiakaki, Eftichia; Dana, Helen; Tragiannidis, Athanasios; Bouka, Evdoxia; et al.
Abstract: Aim: Neuroblastoma outcomes vary with disease characteristics, healthcare delivery and socio-economic indicators. We assessed survival patterns and prognostic factors for patients with neuroblastoma in 11 Southern and Eastern European (SEE) countries versus those in the US, including—for the first time—the Nationwide Registry for Childhood Hematological Malignancies and Solid Tumours (NARECHEM-ST)/Greece. Methods: Overall survival (OS) was calculated in 13 collaborating SEE childhood cancer registries (1829 cases, ∼1990–2016) and Surveillance, Epidemiology, and End Results (SEER), US (3072 cases, 1990–2012); Kaplan–Meier curves were used along with multivariable Cox regression models assessing the effect of age, gender, primary tumour site, histology, Human Development Index (HDI) and place of residence (urban/rural) on survival. Results: The 5-year OS rates varied widely among the SEE countries (Ukraine: 45%, Poland: 81%) with the overall SEE rate (59%) being significantly lower than in SEER (77%; p < 0.001). In the common registration period within SEE (2000–2008), no temporal trend was noted as opposed to a significant increase in SEER. Age >12 months (hazard ratio [HR]: 2.8–4.7 in subsequent age groups), male gender (HR: 1.1), residence in rural areas (HR: 1.3), living in high (HR: 2.2) or medium (HR: 2.4) HDI countries and specific primary tumour location were associated with worse outcome; conversely, ganglioneuroblastoma subtype (HR: 0.28) was associated with higher survival rate. Conclusions: Allowing for the disease profile, children with neuroblastoma in SEE, especially those in rural areas and lower HDI countries, fare worse than patients in the US, mainly during the early years after diagnosis; this may be attributed to presumably modifiable socio-economic and healthcare system performance differentials warranting further research. Highlights: Inequalities in neuroblastoma survival are noted across Southern Eastern Europe (SEE). Poor outcome is related to age >12 months, male gender and location of tumours. Neuroblastoma survival is lower in SEE than that in the US. Rural residence is associated with lower survival in SEE but not in the US. Survival disparities may be due to socio-economic and healthcare system differentials.